Tailoring the Sodium Storage Performance of Carbon Nanowires by Microstructure Design and Surface Modification with N, O and S Heteroatoms. Issue 11 (17th August 2017) - Qiao, Yun; Ma, Mengyue; Liu, Yang; Han, Ruimin; Cheng, Xiaoguang; Li, Qingling; Li, Xiangnan; Dong, Hongyu; Yin, Yanhong; Yang, Shuting
Abstract: The electronic environment and physicochemical property of carbon materials can be easily tailored and modulated by heteroatom doping. Herein, we demonstrate that net‐like N, O, S triple‐doped microporous carbon nanowires (NOS‐MCNs) as an anode can be designed to improve the electrochemical performance of sodium ion batteries. Ammonium persulfate as oxidant can also provide a nitrogen and sulfur source for S‐containing PPy. The N, O and S atoms are introduced into the carbon skeleton with activation and carbonization processes to modify the surface properties. As an anode, the material exhibits a high specific capacity and a long lifespan (≈301 mA h g −1 at 0.2 A g −1 after 1000 cycles) as well as an excellent rate capability (158 mA h g −1 at an extremely high current density of 10 A g −1 ). This work offers a facile strategy to synthesize triple‐doped porous carbon materials for sodium ion batteries and other energy‐storage fields. Abstract : It′s as easy as one, two, three : Microporous carbon nanowires triple‐doped with N, O and S heteroatoms (NOS‐MCNs) were prepared as anode materials to improve the electrochemical performance of sodium‐ion batteries. As an anode, the material exhibits a high specific capacity and a long lifespan (≈301 mA h g −1 at 0.2 A g −1 after 1000 cycles).